Answer:
<h2>(b + 6) (b+ 2)</h2>
Step-by-step explanation:
<em><u>______________________________________________________</u></em>
here we gonna use a rule:
<em><u>if x1 and x2 are rooots of the quadratic equation: ax² + bx + c = 0</u></em>
<em><u>then x1 + x2 = -b/a</u></em>
<em><u>______________________________________________________</u></em>
b^2+ 8b + 12 = (b - b1) (b - b2)
This prove that “b1 = -6” is a root of the quadratic equation b^2+ 8b + 12 = 0
since, the sum of roots b1 + b2 = -8/1 = -8 then b2 = -8 - b1 = -8 - (-6) = -2
then
b^2+ 8b + 12 = (b - (-6)) (b - (-2))
= (b + 6) (b+ 2).
:)